The concept of sustainable development towards multifunctional products - Khairul Azhar Mat Daud; Zulkarnaen Mohd Lajin; Zaini Ashaari; Nik Zulkarnaen Khidzir (2015)
This paper will explain more detail about the way to produce product which is designing and develop by concern the criteria of sustainable. Multipurpose Iron Board is one of the product with applied the concept of sustainability. Multipurpose Iron Board can perform a variety of uses other than iron board itself. In sustainable design, it’s able to function as a ladder and chair too. This product is easy to store, easy to carry, lightweight and durable. In addition, the design of which was developed also emphasized aesthetic values. Ergonomic factors are also taken into account so that the user can use the product properly and safely. Anthropometric data is referenced to ensure product will be produce by full fill the ergonomic factors. This product is designed by considered consumer demand through market survey. The current issue such as limited space and less storage will be overcome through the use of this product.